2017
DOI: 10.31235/osf.io/pc7nw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic status, reputation, and interpersonal trust in peer-to-peer markets: Evidence from an online experiment

Abstract: The increased popularity of peer-to-peer markets decentralizes distribution of resources, a process that can prove to be economically efficient. Yet, this also increases uncertainty about transactions, and therewith the size of the trust problem. Individual characteristics thus become more important in determining who obtains trust as a type of social capital. In light of this societal development, this study is concerned with socioeconomic status as part of the explanans for interpersonal trust. It is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Also scientists employing research methods other than trust game experiments have shown a relationship between social status and perceived trustworthiness. For instance, Keijzer and Corten [32] conducted a vignette experiment designed to simulate peer-to-peer market platforms where participants had to make trusting decisions based on a potential seller's characteristics, including socioeconomic status (education and occupational prestige). Findings showed that higher status led to higher perceived trustworthiness; in addition, they revealed that highstatus individuals were rewarded more for positive reviews for past selling exchanges than low-status actors.…”
Section: Signalling Of Social Status As a Basis For Trustworthinessmentioning
confidence: 99%
“…Also scientists employing research methods other than trust game experiments have shown a relationship between social status and perceived trustworthiness. For instance, Keijzer and Corten [32] conducted a vignette experiment designed to simulate peer-to-peer market platforms where participants had to make trusting decisions based on a potential seller's characteristics, including socioeconomic status (education and occupational prestige). Findings showed that higher status led to higher perceived trustworthiness; in addition, they revealed that highstatus individuals were rewarded more for positive reviews for past selling exchanges than low-status actors.…”
Section: Signalling Of Social Status As a Basis For Trustworthinessmentioning
confidence: 99%
“…For instance, Coleman (1990) suggests that individuals with high socioeconomic status are more likely to be trusted, because they tend to be in positions where they are more visible and opportunistic behavior is more likely to lead to a loss of reputation (also see Ridgeway 2014;Sauder, Lynn, and Podolny 2012). In addition, highstatus individuals may be perceived as more competent and more trustworthy because they are socialized as such during their upbringing and formal education, or conversely, because they would not have achieved a high-status position if they weren't competent and trustworthy (Keijzer and Corten 2017). Regardless of whether such perceptions are true, if they are held by other users, they would imply that providing credible signals of a high socioeconomic status would allow one to appear as more trustworthy, which in itself is a valuable asset in the platform economy (and as such a form of social capital; Coleman 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, linguistic cues could serve as such signals, also in the sense that the usage of language can be seen as a form of cultural capital, that is, a skillset that allows one to identify as a member of the higher socioeconomic strata (Bourdieu 1991). Both qualitative and quantitative empirical research indeed suggest that high-status actors are more likely to be trusted (Keijzer and Corten 2017; but also see Piff et al 2012 for an opposing view), and that linguistic cues play a role in this process (ter Huurne, Moons, et al 2017;Schor et al 2016).…”
Section: Introductionmentioning
confidence: 99%